Enjeux et difficultes du patrimoine naturel et culturel Camerounais : Cas des regions du centre, du sud et de l’est (Sud-Cameroun forestier) - Bela, BC (Vestiges: Traces of Record, 2020)
In developed and developing countries, natural and cultural heritage are used for various purposes. On the one hand, they can help in consolidating political interest or serve as a source of social cohesion while on the other hand, they can serve as a source of economic development and landscape management. In Cameroon, despite the presence of rich material and immaterial [architectural structures, festivals etc.] and natural [dense forests, parks, lakes, cultural sites etc] heritage, the Centre, South and East regions remain relatively unpopular compared to the other regions. Evidence from the field reveal various difficulties encountered in managing these resources as well as their conservation and valorisation. Moreover, beyond political, social and economic setbacks are other difficulties linked to the exploitation of these legacies. As a way forward, this article suggests some pathways to improve on the field situation.